A MATLAB/SIMULINK-BASED INTEGRATED SIMULATION ARCHITECTURE FOR THE STUDY OF RADIONAVIGATION SYSTEMS - Eshmuradov, Dilshod Elmuradovich; Saidova, Gulchehra Erkinovna; Elmuradov, Temurmalik Dilshodovich (SCIENCE and SOCIETY, 2026)
This paper proposes an integrated MATLAB/Simulink-based simulation architecture that enables the study of radionavigation equipment reliability within air traffic management systems, GNSS/INS integration, and multi-agent diagnostic systems within a single software environment. The architecture consists of four interconnected modules – reliability simulation, navigation simulation, interference generation, and multi-agent monitoring simulation – each designed to provide software-based verification of the corresponding scientific results of the dissertation. The data exchange and integration mechanisms between modules are examined, and the composition of the MATLAB toolboxes used in each module is justified. The proposed approach enhances the automation and reproducibility of research in the field of radionavigation systems.
Keywords: radionavigation systems; reliability; Markov chains; GNSS/INS integration; multi-agent monitoring system; MATLAB/Simulink; simulation architecture